Heterosis Analysis of Leaf Stomatal Characteristics on F 1 Population of Cocoa (Theobroma cacao L.) Related to Vascular-Streak Dieback Resistance - Agung Wahyu Susilo; Aida Ainurrachmah; Indah Anita-Sari; Bayu Setyawan; Taryono Taryono (Indonesian Coffee and Cocoa Research Institute, 2017)
Breeding for cocoa resistance to VSD is the main goal in breeding program in Indonesia. Research for selection criteria on cocoa (Theobroma cacaoL.) resistance to vascular-streak dieback (VSD) has being carried out by exploring leaf stomatal characteristics corresponding to VSD damages. This research had objectives to select best crosses by observing the estimated value of heterosis and heterobeltiosis on F1 hybrid populations based on leaf stomata characteristics related to VSD resistance. Trial was established at Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute (ICCRI) in a VSD endemic area. Treatments consisted of 5 F1 hybrid populations generated by biparental crosses of TSH 858(S) x Sulawesi 1 (R), TSH 858 (S) x KEE 2 (R), TSH 858 (S) x Sulawesi 3 (R), Sca 6 (R) x KW 264 (S) and KW 617 (R) x KW 264 (S). Each cross consisted of 100-300 genotypes planted in high planting density of 0.5 m x 0.5 m. Theresistance was evaluated by scoring the plant damage in the scale of 0-3 at three years after planting. Stomata characteristics were assessed microscopically based on the variables of density, length, width and diameter of stomata and width of opening stomata. Analysis of correlation indicated that most of stomatal charac-teristicssignificantly correlated to VSD damage but the width of opening stomata performedthe highest coefficient of correlation (r = 0.49) and contributed to VSD damage (0.45). Meanwhile, path analysis indicated higher value of the char-acteristics performed less resistance of the tested hybrids, KW 617 x KW 264 showed lower value of heterosis and heterobeltiosis for the characteristics which of the best crosses for generating VSD-resistant genotype.